The Concept of Reward and Punishment in Child Education: A Comparative Study between Ibn Sahnun and B.F. Skinner - Jadmiko Aji; Fajhri Prima Vandhi; Antony Mahendra; Benny Prasetya (Al-Hikmah: International Journal of Islamic Studies, 2026)
This study examines the concepts of reward and punishment in child education through a comparative analysis between Muhammad Ibn Sahnun and B.F. Skinner. The study is motivated by the growing crisis of punitive educational practices in contemporary schools, where disciplinary systems are often criticized for being excessively punitive, psychologically harmful, and ineffective in promoting long-term behavioral transformation. Using a qualitative method with a library research approach and a philosophical-comparative perspective, this research analyzes Ibn Sahnun’s Adab al-Mu‘allimin and B.F. Skinner’s Science and Human Behavior as primary sources. The findings reveal that both thinkers acknowledge the importance of behavioral formation through educational intervention; however, they differ fundamentally in their philosophical foundations and educational orientations. Skinner approaches reward and punishment through behavioristic psychology, emphasizing reinforcement, environmental conditioning, and observable behavioral outcomes. In contrast, Ibn Sahnun frames discipline within an ethical-spiritual paradigm aimed at cultivating moral character, religious consciousness, and child welfare. Both perspectives reject arbitrary and excessive punishment, emphasizing corrective and educational discipline instead. Furthermore, this study finds that the integration of Skinner’s behavioral strategies with Ibn Sahnun’s ethical and spiritual principles offers a more balanced framework for contemporary child education. Such integration contributes to the development of educational systems that are not only effective in shaping behavior but also attentive to children’s dignity, emotional well-being, and moral development.